Before and again [compact disc, unabridged] - Delinsky, Barbara (Macmillan Audio, 2018)
Maggie Reid is living a lie, hiding from public scrutiny for a mistake she made years ago. But when standing by a friend could result in uncovering her past, Maggie has a tough choice to make.